Number 13 / Part I. Music. 2. Systematical Approacho of Integrality of Musical Didactical Activity Through The Dramaturgy at Musical Education Lesson - Caliga Marina (Sciendo, 2017)
The integrality of musical-didactical activities at the lesson as a systematical aproach of the musical education process is the problem that we search for. In this way, dramaturgy at the lesson is searched as one of the principles of this integrity. The words "project", "diagram", "scenario", "libretto" of the lesson are described in this study through two aspects: emotional dramaturgy and reasonable dramaturgy. These are the most important purpose of the personal attitude and activity. Through what mechanisms the dramaturgy is obtained at the lesson? How the emotional tones lead to the culmination? How are integrated the words dramaturgy and systematization? All these questions are studied in this article. In this way, dramaturgy at the lesson is the mechanism that integrates the system.